2019
DOI: 10.1097/gco.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum hormonal contraception in breastfeeding women

Abstract: Purpose of review To provide an overview of recent research and guidelines regarding contraception and breastfeeding. Recent findings Recent studies assessed lactogenesis, breastfeeding rates, and milk supply concerns in patients starting postpartum hormonal contraception. One study showed a small but statistically significant increase in milk supply concerns between users and nonusers of postpartum hormonal contraception. Mean time to lactogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The high lack of concern about, or comfort with, breastfeeding while using contraception that we saw in this study has been reported by other researchers as well (Stanton et al, 2019;Weisband et al, 2017). The statistical increase in concern among non-hormonal method users at 6 weeks and 3 months postpartum may not be clinically significant as so few participants reported concerns.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high lack of concern about, or comfort with, breastfeeding while using contraception that we saw in this study has been reported by other researchers as well (Stanton et al, 2019;Weisband et al, 2017). The statistical increase in concern among non-hormonal method users at 6 weeks and 3 months postpartum may not be clinically significant as so few participants reported concerns.…”
Section: Discussionsupporting
confidence: 84%
“…Comfort with initiating contraception while simultaneously initiating breastfeeding must be relayed via the healthcare providers a woman looks to for advice immediately postpartum. This continues to be a struggle (Benfield et al, 2018; Stanton & Blumenthal, 2019). Ensuring women receive the most accurate, up to date information when asking questions regarding contraception and breastfeeding immediately postpartum may still be an area for further research and development.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of progestin-containing LARC placed immediately after delivery demonstrate no effect on lactogenesis, breast milk quantity, exclusive breastfeeding, or infant growth. 6 Immediate postpartum IUD placement is safe and convenient; expulsion risk is higher with IUDs placed less than 10 minutes after delivery (10%-27%) than with interval placement weeks later (2%-10%). 2,7 Although uterine perforation risk is higher with interval IUD placement among breastfeeding or recently postpartum patients, the absolute risk remains low (<1%).…”
Section: Special Considerationsmentioning
confidence: 97%
“…Unintended pregnancies and shorter pregnancy intervals result in maternal and fetal morbidity and mortality, and also increase social and economic burden ( 3 , 4 , 5 ). In various studies, short intervals between pregnancies were found to be associated with increased maternal risks, such as gestational diabetes, placental abruption, and uterine rupture while fetal problems include preterm delivery, low-birth weight or small for gestational age infants ( 6 ) and thus birth-spacing is strongly advised. While the World Health Organization (WHO) recommends an interpregnancy interval (time between delivery and conception of subsequent pregnancy) of 24 months, the American College of Obstetricians and Gynecologists emphasises the importance of avoiding an interpregnancy interval of less than six months and advises an interpregnancy interval of longer than 18 months ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immediate postplacental and early postpartum intrauterine device (IUD) insertion is a convenient and reliable contraceptive method but the expulsion rate is higher than the interval insertion and immediate postplacental IUD insertion requires a trained practitioner ( 12 ). Progestin-bearing hormonal contraceptives (PHC) are effective without any negative impact on lactogenesis, breastfeeding rates, and milk supply during the postpartum period ( 6 , 13 ). PHC implants can also be used during the early postpartum period but insertion and removal requires a visit to a qualified health center, similar to IUDs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%